Al-Haimanah al-Siyāsiyah wa al-Sulṭawiyah fī al-Syi’r al-Inqilāb al-‘Uṡmāny wa Suquṭ al-Sulṭān ‘Abd al-Hamīd li Ahmad Syauqy ‘alā Asās Naẓariyah al-Haimanah li Antonio Gramsci - Etsha Ari Kusuma Dianti; Abdul Basid (Journal of Arabic Literature (JaLi), 2021)
The background of the researcher taking this research topic is because he is interested in studying international conflicts that have occurred and as an additional reference in the world of literature. The purpose of this study is to reveal the forms of political hegemony and power that exist in Ahmad Syauqi's poetry, namely Al Inqilabi Al-Uthmani wa Suquuthi Sulthan Abdul Hamid based on Antonio Gramsci's perspective of hegemony theory and to find the counter-hegemony that existed during the reign of Sultan Abdul Hamid. II. The type of research method used is a qualitative and descriptive research method using a sociological approach. The primary data source used in this research is a poem from a collection of diwans entitled "syauqiyyat", and in it, there are 151 poetry titles. His poem is entitled "Al-Inqilabi Al-Uthmani wa Suquuthi Sulthan Abdul Hamid" by Ahmad Syauqi, while the secondary data sources used are references relevant to the research topic. Data collection techniques used include reading, translation, and note-taking techniques, while the data analysis theory used is the content method. The results obtained describe that (1) There are forms of political hegemony and power over political society and civil society. The following details are found in the political community. There are strategies to attack opponents, threats to subordinates made by superiors, arrangements for maintaining power, and surrender to the authorities. Meanwhile, the application of the form of hegemony in civil society found three forms, namely the government in full power, resistance by discriminated parties, and unilateral decision making by the authorities; (2) This study also reveals the process of counter-hegemony that accompanied the Ottoman coup and the ouster of Sultan Abdul Hamid II found in Ahmad Syauqi's poem, which includes three types of resistance, namely active resistance in the form of demonstrations and coercion of will carried out by the Midhat. Pasha and his colony, passive resistance in the form of negotiation events carried out by Sultan Abdul Hamid II and humanistic resistance by praying and complaining about all actions to Allah SWT by Sultan Abdul Hamid II.